Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1097/icb.0000000000001371
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Retinal Arterial Macroaneurysms Associated with Hemorrhagic Bacillary Layer Detachments

Abstract: Background/Purpose: Bacillary layer detachments (BALAD) are a recently recognized form of retinal detachment involving a splitting of photoreceptors at the inner segment myoid zone, with separation of the external limiting membrane and ellipsoid zone on optical coherence tomography (OCT). A growing number of disease processes are recognized to cause BALAD, and here we present three of the first cases of hemorrhagic retinal artery macroaneurysms that resulted in BALAD.Methods: A retrospective review of three pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Few cases of RAM with haemorrhagic BALAD have been described which resolved with observation, intravitreal tissue plasminogen activator or vitrectomy 10. Here, we describe the first report of RAM-associated BALAD resolving with focal laser.…”
Section: Descriptionmentioning
confidence: 75%
“…Few cases of RAM with haemorrhagic BALAD have been described which resolved with observation, intravitreal tissue plasminogen activator or vitrectomy 10. Here, we describe the first report of RAM-associated BALAD resolving with focal laser.…”
Section: Descriptionmentioning
confidence: 75%
“…26 The hemorrhagic variant of BALAD was first described by Ramtohul et al in a case of proliferative macular telangiectasia Type 2, and subsequent studies reported this OCT finding in nAMD and ruptured retinal arterial macroaneurysms. [27][28][29] On OCT, hemorrhagic BALAD is characterized by accumulation of hyperreflective blood within the cavity formed by the BALAD (i.e., split at the level of the photoreceptor inner segment myoids). 26,27 Its anterior border is marked by the ELM, and the posterior border is represented by a faint EZ corresponding to residual inner and outer segments remaining adherent to the retinal pigment epithelium/Bruch membrane complex.…”
mentioning
confidence: 99%